Penyelesaian Sengketa Tanah Dalam Pengadaan Proyek Jalan Tol Dengan Asas Keadilan - Safaruddin Harefa (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2022)
When the government wants to build a toll road on community land, usually there will be compensation that is charged to the government to pay it to the land owner, but in practice there are often land disputes that will be used in the construction of toll roads, one of which is the unwillingness of the land owner to make it. the land is built toll roads or the land owner does not agree to the compensation paid by the government to him. Whereas in the acquisition of land for toll roads, it is necessary to pay attention to clear stages and in accordance with the applicable legal rules. The stages are starting from the planning stage, preparation stage, implementation stage and the stage of submitting the results of toll road construction. This must be done based on the principles of good governance. Furthermore, the settlement of land disputes for the procurement of this toll road can also be carried out in consultation with the land owner, compensation for the loss of land that is used as the object of toll road construction and the last is through legal channels, namely submission to the court. However, in this case the author places more emphasis on compensation which is more highlighted because compensation prioritizes justice. So before the compensation is implemented, a clear and concrete legal scheme or rule must be made that regulates the scheme and the provision of compensation based on justice